(untitled) (Eurasian Journal of Engineering and Technology, 2022)
Image compression is one of the growing domains in image processing. Using these compression strategies as a foundation, this paper examines several robust methods for image compression and the kinds of pressure used to reduce the importance of data in a smaller medium. This study is classified and analyzed according to the two basic kinds of studies: lossy compression and lossless compression. Multiple transactions of each kind have been performed to determine the compression efficiency of compressed files. As decided by previous research, the advantages and cons of each variety will likewise be provided.